Bladder neoplasms and NF-κB: an unfathomed association. (3rd May 2020) - Walter, Charles Emmanuel Jebaraj; Durairajan, Sankari; Periyandavan, Kalaiselvi; C, George Priya Doss; G, Dicky John Davis; A, Hannah Rachel Vasanthi; Johnson, Thanka; Zayed, Hatem
ABSTRACT: Introduction : Bladder cancer is the second most common genitourinary tract cancer and is often recurrent and/or chemoresistant after tumor resection. Cigarette smoking, exposure to aromatic amines, and chronic infection/inflammation are bladder cancer risk factors. NF-κB is a transcription factor that plays a critical role in normal physiology and bladder cancer. Bladder cancer patients have constitutively active NF-κB triggered by pro-inflammatory cytokines, chemokines, and hypoxia, augmenting carcinogenesis and progression. Areas covered : NF-κB orchestrates protein interactions (PTEN, survivin, VEGF), regulation (CYLD, USP13) and gene expression (Trp 53) resulting in bladder cancer progression, recurrence and resistance to therapy. This review focuses on NF-κB in bladder inflammation, cancer and resistance to therapy. Expert opinion : NF-κB and bladder cancer necessitate further research to develop better diagnostic and treatment regimens that address progression, recurrence and resistance to therapy. NF-κB is a master regulator that can act with or on minimally one cancer hallmark gene or protein, leading to bladder cancer progression (Tp53, PTEN, VEGF, HMGB1, CYLD, USP13), recurrence (PCNA, BcL-2, JUN) and resistance to therapy (P-gp, twist, SETD6). Thus, an understanding of bladder cancer in relation to NF-κB will offer improved strategies and efficacious targeted therapies resulting in minimal progression, recurrence and resistance to therapy.